Kajian Kelelahan Kerja Dan Lingkungan Fisik Pada Home Industri Tahu - Fajri, Rahmad; Helmy, Helina; Usman, Sarip; Sutopo, Agus; Kadarusman, Haris (MIDWIFERY JOURNAL, 2024)
Backgorund: Work fatigue is a feeling of tiredness and decreased alertness. From a neurophysiological point of view, it is revealed that fatigue is seen as a systematic state of the central nervous system resulting from prolonged activity and is fundamentally controlled by opposing activity between the activity system and the inhibition system in the brain stem. purpose: From this research to determine the temperature, lighting and humidity in the Tahu Home Industry, Gunung Sulah Village, Bandar Lampung City. Methods: This research is descriptive, namely direct observation in the field. The objects of this research are 7 tofu home industries located on Mount Sulah, data obtained through temperature and humidity measuring devices (Thermohygrometer), lighting (Lux meter), as well as checklists and questionnaires for work fatigue.Results: Obtained from seven tofu industries that have not fully met the requirements or 100％ none of them have met the requirements as decided by Minister of Health Regulation No. 70 of 2016. The measuring instruments used are temperature, humidity (Thermohygrometer), Lighting (Lux meter) and of the thirty-five respondents, twenty-five workers are affected by health problems, namely Heat strain, Heat Exhaustion and Heat Stroke, while work fatigue is excessive, namely never 0%, Rarely 2.85%, Sometimes 11.42%, Often 85.71%, Very often 0%.Conclusion: The author hereby suggests that every home industry owner should control environmental factors in accordance with the need for a comfortable and safe workplace for workers.Suggestion: It would be best for every home industry owner to know to add ventilation or fans to minimize high temperatures in the workplace to create good air circulation, add lighting in the form of lamps or natural lighting, and prepare drinks for workers so that lost body fluids can be replaced with drink lots of water Keywords: Temperature, Lighting, Humidity and Work Climate ABSTRAK Latar belakang: Kelelahan kerja adalah rasa penat serta berkurangnya kewaspadaan. Berdasarkan perspektif neurofisiologi, kelelahan dianggap sebagai kondisi sistem saraf pusat yang disebabkan oleh kegiatan tanpa henti, yang secara mendasar dikendalikan oleh interaksi kontradiktif antara koordinasi aktifitas dan sistem supresi di batang otak.Tujuan: Dari penelitian ini untuk mengetahui Suhu, Pencahayaan, Kelembaban dan kelelahan kerja pada Home Industri Tahu Kelurahan Gunung Sulah Kota Bandar Lampung.Metode: Penelitian ini bersifat deskriptif yaitu observasi langsung ke lapangan. Objek pada penelitian ini adalah tujuh home industri tahu yang berada di Gunung Sulah, data yang diperoleh melalui alat pengukur suhu dan kelembaban (Thermohygrometer), pencahayaan (Lux meter), serta cheklist dan kuisioner untuk kelelahan kerja.Hasil: Diperoleh dari tujuh industri tahu belum memenuhi syarat sepenuhnya atau 100％ tidak ada yang memenuhi syarat sesuai yang diputuskan oleh Permenkes No. 70 Tahun 2016. Alat ukur yang di gunakan yakni suhu, kelembaban (Thermohygrometer), Pencahayaan (Lux meter) dan dari tiga puluh lima responden dua puluh lima pekerja terkena gangguan kesehatan yakni Heat strain, Heat Exhaustion, dan Heat Stroke sedangkan untuk kelelahan kerja secara berlebih yakni tidak pernah0%, Jarang 2,85%, kadang-kadang 11,42%, Sering 85,71%, Sangat sering 0%.Kesimpulan: Dengan ini penulis menyarankan untuk tiap pemilik home industri agar dilakukannya pengendalian faktor lingkungan sesuai dengan kebutuhan tempat bekerja yang tentram dan terjaga bagi pekerja.Saran: sebaiknya untuk tiap pemilik home industri tahu menambahkan ventilasi atau kipas angin untuk meminimalisir suhu yang tinggi di tempat kerja agar terciptanya sirkulasi udara yang baik, menambahkan penerangan berupa lampu ataupun berupa pencahayaan alami, dan menyiapkan minum untuk para pekerja agar cairan tubuh yang hilang bisa digantikan dengan minum air putih yang banyak. Kata Kunci: Suhu, Pencahayaan, Kelembaban Dan Iklim Kerja